Vaccination against SARS-CoV-2 in Guinea-Bissau - Cardoso, Plácido (2022)
Vaccination is defined as one of the safest ways to protect against COVID-19 and has been the focus of the world’s health authorities since the beginning of the pandemic. Scientists have dedicated research to the viruses causing the infection as well as to the discovery of the respective vaccines.In the case of Guinea-Bissau, the availability of vaccines was not critical but the reluctance of the population to be vaccinated in view of rumours, phobias and fears about the vaccine and its consequences on the body, especially if you consider the gender aspect, in which it has been mentioned that the vaccination against COVID-19 causes infertility in women of childbearing age and/or other fake news that report death after 2 years of having been vaccinated. Routine vaccination activities were guaranteed with the gradual establishment of vaccination centres in the Autonomous Sector of Bissau (SAB), which evolved from 3 to 14 centres/posts with the active participation of military health technicians after the signing of a partnership agreement.Another relevant aspect to note in the vaccination process against COVID-19 was the digitalisation of the process and the issuing of the vaccination certificate. Despite all these constraints, one year later (april 2021) after the start of vaccination activities the country has reached 50%  coverage of the target population, i.e. the population aged 18 years or older, fully vaccinated and 76% of the same population with at least one dose. It is envisaged that vaccination will soon be extended to the adolescent population between 12 and 17 years of age in light of the revision of the National Vaccination Plan (1) and funding opportunities from partners such as the World Bank with the introduction of new vaccines such as MODERNA in the vaccination programme against COVID19. It should be recalled that to date the following vaccines have been used: Astrazeneca, Jansen and Sinopharma.